PENGARUH PENAMPILAN MODIS TERHADAP PENGEMBANGAN KARIR KARYAWAN PEREMPUAN PADA BANK DANAMON CABANG PEKANBARU - Ainun Mardiah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2010)
Fashionable and attractive appearance is a requirement that priority for employees in the banking world. Fashionable appearance is always interpreted as a way of dress, makeup, lifestyle, and selfactualization as a whole is quite attached to women employees in public life. Research conducted on 30 female employees at PT Pekanbaru Danamon Bank. It focuses on the issue of whether the appearance of fashionable significant effect on female employees' career development. The results showed that the appearance of fashionable significant impact on employee career development of women in PT Pekanbaru Damon Bank.